Analysis of The Influence of Price, Digital Advertising and E-Service Quality on Digital Repurchase Intention of Online Travel Platform Users - Sudirjo, Frans; Setyo Oetomo, Dedy; Grace Putrianti, Flora; Abubakar, Faisal; Lamboy Sinaga, Victor (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to assess the effects of price, e-service quality, and advertising on online travel agent users' propensity to repurchase. Convenience sampling was used to select 100 respondents to serve as study participants, giving us the research sample. Through observations, questionnaires, and interviews, we gathered data. The primary technique for data analysis employed by the researchers was multiple linear regression, and they employed a descriptive study design. Important results show that repurchase intention is significantly influenced by advertising. The price variable, which exhibits a strong influence on repurchase intention, experiences the same phenomenon. Repurchase intention is also significantly influenced by the quality of the e-service. These findings corroborate the hypothesis that consumers of online travel agencies have a propensity to repurchase based on factors such as price, advertising, and e-service quality. Additionally, the study's findings show that the combination of these three factors pricing, e-service quality, and advertising significantly affects repurchase intention. This suggests that consumers repurchase intentions on the online travel agent platform can be raised by a clever combination of advertising-based promotion, competitive pricing, and high-quality online services. The development of marketing and customer service initiatives in the online travel agency sector can benefit greatly from these findings.